THE TRADITION OF ZULLISANAYNISM AT THE END OF HE 19th CENTURY AND THE BEGINNING OF THE 20th CENTURY (IN THE EXAMPLE OF WORKS OF NODIM, KHILVATI, KHAYRATI) (Scientific journal of the Fergana State University, 2023)
At the end of the 19th century and at the beginning of the 20th century, the tradition of Zullisonayn reached a new level. In the same period, there was a period of changes in literature, literally, renewal. Because by this time, jadidism had appeared as a very broad and active movement in social life. This had a direct impact on literature. In our article, we tried to shed light on the new image of this evolution ad the new interpretation of the Zullisonayn tradition.